Is diabetes associated with increased pathological burden in Alzheimer's disease?. Issue 1 (10th November 2021) - Sadrolashrafi, Kaviyon; Craft, Suzanne; Decourt, Boris; Adem, Abdu; Wilson, Jeffrey R.; Miller, Justin; Sabbagh, Marwan N.
Abstract: Introduction: We examined the association between Alzheimer's disease (AD) and type 2 diabetes mellitus (DM) and hypothesized that diabetes is associated with an increased pathological burden in clinically and pathologically diagnosed AD. Methods: All data were obtained from the Uniform Data Set (UDS) v3, the Neuropathology Data Set, and the Researcher's Data Dictionary‐Genetic Data from the National Alzheimer's Coordinating Center. The dataset (37 cases with diabetes and 1158 cases without) relies on autopsy‐confirmed data in clinically diagnosed AD patients who were assessed for diabetes type in form A5 or D2 during at least one visit. Differences in scores were explored using a general linear model. Effect sizes were calculated using sample means and standard deviations (Cohen's d ). Results: The presence of diabetes was associated with a lower Thal phase of amyloid plaques (A score; 4.6 ± 0.79 vs. 4.3 ± 0.85, P < .05) and lower Braak stage for neurofibrillary degeneration (B score; 5.58 ± 0.72 vs. 5.16 ± 0.96, P < 0.05) but not for density of neocortical neuritic plaques (CERAD score‐C score). The National Institute on Aging–Alzheimer's Association Alzheimer's disease neuropathologic change (ABC score) was not different between AD+DM and AD‐DM. Discussion: This pilot study found a significantly lower Thal phase of amyloid plaques and Braak stage for neurofibrillary degeneration in AD‐confirmed individuals with diabetes compared to those without. Thus type 2 DM is not associated with increased AD pathology in clinically and pathologically confirmed cases of AD.